Ayman al-Zawahiri and the Challenges of Succession in Terrorist Organizations - Mendelsohn, Barak (Terrorism and political violence, 2022)
What challenges do newly appointed terrorist leaders face? The paper proposes four primary needs all new leaders consider, including acceptance by the organization’s members, assuming control, maintaining organizational coherence and unity, and overcoming counterterrorism pressures. The magnitude of each challenge may differ depending on the predecessor’s character, the organization’s institutionalization level, the group’s ideological and strategic coherence, the availability of material resources, and communal support. This analytical framework is then used to assist the paper’s second objective: understanding how Ayman al-Zawahiri, who succeeded bin Laden, negotiated these challenges and the tradeoffs he made. Shifts in Al Qaeda’s operational environment required al-Zawahiri to confront challenges more complex than his predecessor had faced, even as he had fewer tools to solve them. Facing authority crisis, magnified by the incoherence between Al Qaeda’s central leadership and its branches and Al Qaeda’s inability to control its branches, al-Zawahiri increased decentralization, embraced affiliates’ local focus, promoted efforts to raise Al Qaeda’s local appeal, and sought to reduce U.S. interest in targeting the group. He kept Al Qaeda alive, but saw its stature shrink significantly.